Konstruktivisme sebagai Implementasi Pembelajaran PAI - Choirul Anam; Fiqhi Afifa (CENDEKIA, 2021)
Humans who work as teachers or teachers will look for various methods that are suitable for use in the pedagogy and learning process, so that students can learn well. Constructivism method is a process where the source of knowledge, from experience or real reality on the individual or the students themselves. So that in the learning process students or students explore their own knowledge, the teacher only fishes or makes a scenario of a problem about the material presented so that students can automatically think about solving the problems given by the teacher. Good learning is one that is able to grow the enthusiasm and interest in learning of students to increase. Belong of them is the sense of compatibility and interest between students and good and fun learning methods. Researchers think the Constructivism method as the implementation of PAI learning is very useful, for the advancement of the thinking power of students in the educational process, especially in PAI subjects. Keywords: Constructivism, PAI Learning Implementation